Atomic scale modelling of the cores of dislocations in complex materials part 1: methodology - Gale, Julian; Wright, Kathleen; Walker, A.; Slater, B. (Royal Society of Chemistry, 2005)
Dislocations influence many properties of crystalline solids, including plastic deformation, growth and dissolution, diffusion and the formation of polytypes. Some of these processes can be described using continuum methods but this approach fails when a description of the structure of the core is required. To progress in these types of problems, an atomic scale model is essential. So far, atomic scale modelling of the cores of dislocations has been limited to systems with rather simple crystal structures. In this article, we describe modifications to current methodology, which have been used for strongly ionic materials with simple structures. These modifications permit the study of dislocation cores in more structurally complex materials.